Portfolio of compositions: "an exploration of musical composition and sound production in the context of cross-disciplinary performance" - Caillouët, Jean-David (The University of Edinburgh, 2007)
Growing up in a non-musical family, the type of music I first encountered was popular music. My early interest in music therefore came from listening to recordings where the quality of the sound forms an essential part of the listening experience. I was also fascinated by the sounds and music I heard in the cinema.

As my curiosity developed I gradually became more interested in many other areas of music making and musical styles, experimenting with sounds at any given opportunity.

1 embarked on this PhD in October 2000 having just completed an Honours Degree in Music at Dartington College of Arts, Devon. During that period of study, I became acquainted with various studio techniques, using both analogue and digital equipment. I felt I had found an adequate territory in which to express my musical creativity. I was therefore very interested in continuing to explore the potential offered by musical technology and to broaden my skills as a music maker, recording artist and producer.

My aim for this research was to develop my knowledge of technology, developing recording techniques in order to reproduce the sounds I had grown up with as well as discovering new sonic possibilities in the process.

I also conceived this PhD as an opportunity to explore cross-disciplinary practices, with the idea of developing collaborations with artists working in other media.

I hope to present, with the works included in this portfolio, a clear illustration of the path I have undertaken during the last five years.